SAT0159 Clinical Features of Japanese Patients with Vasculo- BehÇEt'S Disease: A Multicenter Study by BehÇEt'S Disease Research Committee, MHLW. (23rd January 2014) - Takeno, M.; Ideguchi, H.; Suda, A.; Watanabe, R.; Kikuchi, H.; Nagafuchi, H.; Kuwana, M.; Saito, K.; Hirohata, S.; Ishigatsubo, Y.
Abstract : Background: Vascular lesion is one of most critical manifestations in patients with Behçet's disease (BD), whereas there are some regional differences in the clinical features. Objectives: This study characterizes clinical features and therapeutic approaches in Japanese vasculo-BD patients. Methods: We retrospectively analyzed clinical data of 105 BD patients (male 71, female 34) with vascular lesions from 6 institutes which belong to Behçet's Disease Research Committee, Ministry of health, labor, and Welfare, Japan. All patients met the Japan Diagnostic Criteria (2003), and presented with more than one vascular lesions in arteries and veins, but superficial thrombophlebitis was not included as vascular involvement. Results: The diagnosis of BD in the enrolled patients was made at 35.5 years old, while the initial vascular event appeared at 42.7 years old. Frequency of HLA-B51 positive was lower in vasculo-BD patients (41%) than the others (51%). Eye involvement and epididymitis were less frequent in vasculo-BD patients, whereas intestinal lesions were more commonly found. The vascular lesions were distributed in the venous system (71%), the arterial system (31%) and the pulmonary vessels (25%), all of which were determined by imaging modalities including contrast CT, angiography, ultrasonography, pulmonary perfusion scan, MRI, and PET. As treatment, corticosteroids and immunosuppressants such as MTX, cyclosporine, and azathioprine were used in 73% and 35%, respectively, whereas 18 patients (17%) had surgical operation. Of 5 patients treated with Infliximab, 2 patients received endovascular or surgical intervention for the vascular lesions, resulting in improvement. Any anticoagulant and/or anti-platelet agents were used in 82.9 % of patients, including warfarin in 58.1% and aspirin 49.5%. These agents-related bleeding events were found 9 times in 8 patients, all of them were minor and recovered after discontinuation of the agents. Eight patients have died, and 4 of them were associated with vascular involvement including hemoptysis in 2 patients who did not receive anticoagulant and anti-platelet agents. Conclusions: The present study shows that the distribution of vascular lesions and therapeutic approaches in Japanese BD patients were similar with those from other countries according to previous reports. However, our data suggest that fatal pulmonary bleeding caused by anticoagulant and anti-platelet agents is rare in Japanese BD patients, though these agents are commonly used in Japan. Disclosure of Interest: None Declared